If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5c = 1 + -1c(x + 2) Reorder the terms: -5c + 2x = 1 + -1c(x + 2) Reorder the terms: -5c + 2x = 1 + -1c(2 + x) -5c + 2x = 1 + (2 * -1c + x * -1c) -5c + 2x = 1 + (-2c + -1cx) Solving -5c + 2x = 1 + -2c + -1cx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2c' to each side of the equation. -5c + 2c + 2x = 1 + -2c + 2c + -1cx Combine like terms: -5c + 2c = -3c -3c + 2x = 1 + -2c + 2c + -1cx Combine like terms: -2c + 2c = 0 -3c + 2x = 1 + 0 + -1cx -3c + 2x = 1 + -1cx Add 'cx' to each side of the equation. -3c + cx + 2x = 1 + -1cx + cx Combine like terms: -1cx + cx = 0 -3c + cx + 2x = 1 + 0 -3c + cx + 2x = 1 Add '-2x' to each side of the equation. -3c + cx + 2x + -2x = 1 + -2x Combine like terms: 2x + -2x = 0 -3c + cx + 0 = 1 + -2x -3c + cx = 1 + -2x Reorder the terms: -1 + -3c + cx + 2x = 1 + -2x + -1 + 2x Reorder the terms: -1 + -3c + cx + 2x = 1 + -1 + -2x + 2x Combine like terms: 1 + -1 = 0 -1 + -3c + cx + 2x = 0 + -2x + 2x -1 + -3c + cx + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 -1 + -3c + cx + 2x = 0 The solution to this equation could not be determined.
| 9d-1=-6d-31 | | 12n+13= | | 7q=15+11q-3 | | -5m-24=m | | 3x-1=7+x | | y=2+lnx | | X+870=2x+870+8570-14150 | | x(3)+x-4(1.50)+4(1.50)=55.80 | | 3(2x-4)=20(5-3x) | | 3(x-2)=10(5-3x) | | 2x+870+8570=2x+870+8570+14150 | | (3x-1)+(y+5)i=1-3i | | 3x+y+5*4i=2 | | 10(d+4)=40 | | 12-(4x-3)=30 | | 32=17 | | 3(2y-7)=9 | | 6-9x=-3 | | -(x-9)=-x-9 | | -(x-7)=-x-7 | | 3x-(5x-(105-30x)-35)=12 | | 8x+16=56-2x | | lg(2x)=-1 | | 24=8x+6y | | 9-4y=-5y | | 41+13x=37+8x+8 | | 0,1x-10=30 | | 5(3w+7)=-32 | | X^2=1.93 | | 4534543534534+4353434534= | | x(x-5)=176 | | (x-5)(x+4)=(x+7)(x-6) |